Information System for Public Complaints at the Industrial Department of Samarinda City - Nur Linda; Asep Nurhuda; Fajar Ramadhani (TEPIAN, 2022)
In the reporting system at the Department of Industry of Samarinda City, reports on problems from the community are distributed to related parties collectively and manually, so the submission process tends to be long. Submission of long reports has an impact on the slow response from the government to the community. In addition, the process of distributing reports manually means that the public does not know how the government will follow up on the report. Therefore, this research aims to help the community in terms by submitting complaints or suggestions to the Samarinda City Industry Office and to assist the Samarinda City Industry Office to serve the community in terms of answering public complaints. The results of this study can facilitate the work of the Samarinda City Industry Office in viewing complaints from Samarinda City residents via the Web and can be monitored online by the Admin. In addition, residents of Samarinda City can voice their aspirations freely and easily without having to go to the Samarinda City Industry Office